Effect of canopy cover on growth of Erythrophleum fordii in enrichment planting for forest restoration in Northeast Vietnam - NGUYEN TRONG MINH; NGUYEN TOAN THANG; DAO TRUNG DUC; TRAN HOANG QUY; HOANG VAN THANH; TRINH NGOC BON; DANG VAN THUYET; LE SY DOANH; TRAN VAN DO (Smujo International, 2026)
Abstract. Minh NT, Thang NT, Duc DT, Quy TH, Thanh HV, Bon TN, Thuyet DV, Doanh LS, Do TV. 2026. Effect of canopy cover on growth of Erythrophleum fordii in enrichment planting for forest restoration in Northeast Vietnam. Asian J Agric 10 (2): g100207. https://doi.org/10.13057/asianjagric/g100207. Erythrophleum fordii is a valuable native species for restoring degraded tropical forests in Vietnam, yet suitable light conditions for enrichment planting remain poorly understood. This study evaluated whether the growth and stem quality differed among observed canopy environments on the growth performance and stem quality of E. fordii 4.5 years after planting in Northeast Vietnam. Three growing conditions were compared: moderate canopy cover (0.3-0.4), dense canopy cover (0.6-0.7), and bare land. Results showed that bare land conditions produced the highest diameter growth (D₁.₃ = 3.40 ± 0.21 cm) and height (H = 3.3 ± 0.12 m), while moderate canopy cover yielded intermediate growth (D₁.₃ = 1.44 ± 0.12 cm, H = 2.2 ± 0.13 m) with the highest proportion of good-quality stems (47.4%). Dense canopy cover resulted in significantly reduced growth (D₁.₃ = 0.86 ± 0.08 cm, H = 1.3 ± 0.08 m) and stem quality (6.2% good stems). Strong positive correlations between diameter and height (R² = 0.77-0.82) under forest canopy indicated consistent allometric relationships, while bare land conditions showed weaker correlations (R² = 0.53). These findings suggest that E. fordii exhibits shade tolerance suitable for enrichment planting under moderate canopy openness (0.3-0.4), balancing growth rate with stem quality for sustainable forest restoration in degraded evergreen broadleaf forests of Northeast Vietnam. It should be noted, however, that treatments in this study represent single contiguous planting areas rather than replicated experimental plots; results should therefore be interpreted as observed associations among canopy environments rather than fully replicated experimental outcomes.